Does ICT contribute to labor productivity? an industry-level analysis of the relationshop between ICT investments and labor productivity in the Philippines - Cruz, Karisha Anne E.; Jandoc, Karl Robert L. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
This paper investigates the relationship between ICT hardware and software investments, and labor productivity using a panel data of Philippine industry groups in 2010 to 2015. The study employs random effects models to analyze the panel data. To account for possible sample selection bias, the study uses a Heckman two-step estimator of the full model. Additionally, this paper measures the differentiating effect of ICT when considering industry-specific characteristics (i.e., average firm age, employment size, education, foreign capital participation, corporations, and export-oriented). The findings suggest that industries are more likely to increase labor productivity by investing in ICT software and database systems. The results further provide evidence of the differentiating effect of ICT investments by various industry-specific characteristics. Employment size and share of foreign ownership strengthen the effect of ICT hardware on productivity. Meanwhile, age and share of exporting firms negatively influence the effect of ICT software and hardware, respectively. Both ICT hardware and software investments have no differentiating effect by share of high school workers and share of corporations.
Thesis (Master in Development Economics) -- University of the Philippines Diliman
Keywords: Information technology -- Economic aspects -- Philippines; Information techology -- Labor productivity -- Philippines